PERIPHERAL CEMENTO-OSSIFYING FIBROMA – A CASE REPORT - GOPAL K, SARASWATHI; R, SANGAVI; L, ARATHY (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Peripheral cemento-ossifying fibroma is a gingival overgrowth that occurs most commonly on the gingiva. It is a slow-growing reactive lesion. It is a benign tumor that grows to a considerable size and leads to pathologic migration of the teeth at later stages. It most commonly occurs following a gingival irritation or trauma. These lesions are said to arise from the PDL fibers excision of these lesions along with the periosteum is very important to avoid recurrence. The recurrence rate of peripheral cemento-ossifying fibroma has been reported to be 8–20%, so a close postoperative follow-up is required. Here, we are presenting two case of peripheral cemento-ossifying fibroma in the mandible.